2019
DOI: 10.1016/j.foodchem.2018.07.154
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the extraction temperature on polyphenolic profiles and bioactivity of chamomile (Matricaria chamomilla L.) subcritical water extracts

Abstract: The main goal of this research was to determine the relationship among chemical structure, bioactivity and temperature of chamomile during subcritical water extraction in isobaric conditions (45 bar) at seven different temperatures (65-210 °C). The influence of temperature on phenolic profiles was defined by UHPLC-HESI-MS/MS. The overall results indicate that the presence of conjugated double bonds, side chains, glucose moiety or ether moiety in molecules influence the efficiency of polyphenols' extraction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 32 publications
4
27
0
3
Order By: Relevance
“…According to the results, the highest amount of TP was obtained when ultrasound was used as a pretreatment, and temperature, pressure, and time were 150°C, 40 bar, and 30 min, respectively. Similar results have been obtained for the grape skin (Duba, Cassaza, Mohamed, Perego, & Fiori, ), ginseng (Zhang et al, ), and chamomile (Cvetanovic et al, , ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…According to the results, the highest amount of TP was obtained when ultrasound was used as a pretreatment, and temperature, pressure, and time were 150°C, 40 bar, and 30 min, respectively. Similar results have been obtained for the grape skin (Duba, Cassaza, Mohamed, Perego, & Fiori, ), ginseng (Zhang et al, ), and chamomile (Cvetanovic et al, , ).…”
Section: Resultssupporting
confidence: 80%
“…Furthermore, Cvetanovic et al () reported that optimum temperature to achieve the highest antioxidant activity in chamomile was 150°C. In another study by Cvetanovic et al (), it was shown that the best pressure for the extraction of the phenolic compounds from chamomile was between 30 and 45 bar.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there is no universal procedure for herbal infusion preparation that is proper for the extraction of antioxidant compounds [18]. There are a few works reporting the influence of extraction temperature on bioactivity [17,19] and acute toxicity [5] of herbal aqueous extracts.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the sample preparation for the detection of cyclitols and sugars, honey samples can be easily handled, since just a dilution in water is required. Conversely, for the analysis of cyclitols and sugars from plant material, an elaborated procedure is required in terms of both, the solvent used and the extraction techniques [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%